Pendidikan akhlak persfektif Ibnu Taimiyah: Analisis Kitab Tazkiyatun Nafs - Sulhan, Sulhan (Tawazun: Jurnal Pendidikan Islam, 2022)
The main emphasis of education in Indonesia is still more on the cognitive process, and less on the morals and character of students. Thus, there are still many students who have bad morals in their lives. This study aims to analyse moral education extracted from the Book of Tazkiyatun Nafsi by Ibn Taymiyyah. The method used in this research is qualitative with a literature study approach and primary data sourced from the book Tazkiyatun Nafsi by Ibn Taymiyyah. The results of the study revealed that Ibn Taimiyah's concept of moral education was born as a form of response to the state of faith and morals of the local community at that time, where the community at that time was increasingly damaged and destroyed. The scope of moral education in the book of Tazkiyatun Nafsi Ibn Taimiyah includes the material of sincerity, piety, amar makruf nahi mungkar, shame, noble and generous, repentance, praise and gratitude, honesty, patience, iffah, jealousy, prayer, khosyah, at-tadzkir, husnudzon (being kind), tawaddhu (humble), tawakkal, obedience, and ridha. Abstrak Titik berat pendidikan di Indonesia masih lebih banyak menekankan pada proses kognitif, dan kurang memperhitungkan akhlak dan budi pekerti siswa. Sehingga, masih banyak siswa yang memiliki akhlak yang tidak baik dalam kehidupannya. Penelitian ini bertujuan untuk menganalisis pendidikan akhlak yang digali dari Kitab Tazkiyatun Nafsi Karya Ibnu Taimiyah. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan studi pustaka dan data primer yang bersumber dari kitab Tazkiyatun Nafsi karangan Ibnu Taimiyah. Hasil penelitian mengungkapkan bahwa konsep pendidikan akhlak Ibnu Taimiyah lahir sebagai bentuk respons keadaan akidah dan akhlak masyarakat setempat pada waktu itu, di mana masyarakat pada saat itu akhlaknya yang semakin rusak dan hancur. Ruang lingkup pendidikan akhlak dalam kitab Tazkiyatun Nafsi Ibnu Taimiyah mencakup materi ikhlas, takwa, amar makruf nahi mungkar, malu, mulia dan dermawan, taubat, pujian dan syukur, jujur, sabar, iffah, rasa cemburu, doa, khosyah, at-tadzkir, husnudzon (berbaik sangka), tawaddhu (rendah hati), tawakkal, taat, dan ridha.